2016
DOI: 10.1063/1.4956453
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Energy transfer and reaction dynamics for DCl scattering on Au(111): An ab initio molecular dynamics study

Abstract: Scattering and dissociative chemisorption of DCl on Au(111) are investigated using ab initio molecular dynamics with a slab model, in which the top two layers of Au are mobile. Substantial kinetic energy loss in the scattered DCl is found, but the amount of energy transfer is notably smaller than that observed in the experiment. On the other hand, the dissociative chemisorption probability reproduces the experimental trend with respect to the initial kinetic energy, but is about one order of magnitude larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 29 publications
4
49
1
Order By: Relevance
“…From Ref. 104 , which also used the RPBE functional, a change of 0.07 can be extracted at ! F¬±Å² = 2.5 eV (the energy transferred to the surface was about 1100 meV).…”
Section: Aimd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Ref. 104 , which also used the RPBE functional, a change of 0.07 can be extracted at ! F¬±Å² = 2.5 eV (the energy transferred to the surface was about 1100 meV).…”
Section: Aimd Resultsmentioning
confidence: 99%
“…Reaction probabilities presented for DCl in Ref. 104 and vibrational motion of DCl in the gas phase. As will be shown below, however, the computed reaction probability critically depends on the initial conditions.…”
Section: Aimd Resultsmentioning
confidence: 99%
“…The AIMD approach has very recently been used successfully in studying HCl scattering and dissociation on Au(111). 51,52 In addition to the AIMD studies, we have also carried out AIMD with electronic friction (AIMDEF) 47,53,54 calculations in which the possible involvement of EHPs in the energy dissipation of hot H atoms is explored with the LDFA approach. 48 The AIMDEF approach eliminates the uncertainties in the previous empirical treatment of the EHP effects.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to reproduce such sticking data from theory has shown that dissipation from phonons can require in some cases an explicit treatment of substrate motion, while satisfactory agreement is often already achieved on the level of effective energy sink models, or even a complete neglect of energy exchange with the lattice. While some prediction of the phononic relevance can be made based on the adsorbate-substrate mass mismatch, this does not always appear to be accurate [78,86,92]. This uncertainty adds yet another facet of complexity when considering also the contributing role of the non-adiabatic dissipation channel, whose relevance remains to date similarly obscure and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…A prototypical such example is the dissociation of HCl on Au(1 1 1) for which energy dissipation is believed to play a key role [91]. While (independently performed) AIMD simulations [86,92] have consistently overestimated the experimental probabilities [91], the corresponding reaction dynamics of this system remain an enigma and have become quite a controversy in the field [86].…”
Section: Explicitly Resolving Surface Motionmentioning
confidence: 99%